2015
DOI: 10.1523/jneurosci.1671-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Task-Related Plasticity of Spectrotemporal Receptive Fields in the Auditory Midbrain

Abstract: Previous research has demonstrated that auditory cortical neurons can modify their receptive fields when animals engage in auditory detection tasks. We tested for this form of task-related plasticity in the inferior colliculus (IC) of ferrets trained to detect a pure tone target in a sequence of noise distractors that did not overlap in time. During behavior, responses were suppressed at the target tone frequency in approximately half of IC neurons relative to the passive state. This suppression often resulted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
117
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(132 citation statements)
references
References 46 publications
15
117
0
Order By: Relevance
“…Our training paradigm additionally combined high-variability stimuli and reinforcement driven learning via trial-by-trial feedback; training components found to direct participant attention to category-relevant acoustic cues and lead to long-lasting behavioral retention [3436]. Animal models have demonstrated that receptive field properties of neurons in the primary auditory cortex (A1) [37, 38] and the inferior colliculus [39] undergo task-related changes in stimulus-response strength as a result of associative learning. These changes have been connected to dopaminergic projections to A1, activated by associations between incoming stimuli and reinforcers (e.g., reward or punishment) [40, 41].…”
Section: Discussionmentioning
confidence: 99%
“…Our training paradigm additionally combined high-variability stimuli and reinforcement driven learning via trial-by-trial feedback; training components found to direct participant attention to category-relevant acoustic cues and lead to long-lasting behavioral retention [3436]. Animal models have demonstrated that receptive field properties of neurons in the primary auditory cortex (A1) [37, 38] and the inferior colliculus [39] undergo task-related changes in stimulus-response strength as a result of associative learning. These changes have been connected to dopaminergic projections to A1, activated by associations between incoming stimuli and reinforcers (e.g., reward or punishment) [40, 41].…”
Section: Discussionmentioning
confidence: 99%
“…Physiological studies have demonstrated that spectro-temporal modulation tuning of midbrain inferior colliculus neurons (Slee and David, 2015) and cortical neurons (Fritz et al, 2003) are modified when an animal engages in an auditory detection task, producing changes that enhance discriminability of task-relevant sounds. Our findings, demonstrating the unique use of spectro-temporal cues in CI users, provide evidence that auditory plasticity and adaptation to CI processing strategies in adults who became deaf has the potential to enhance detection of cues that are involved in speech understanding.…”
Section: Discussionmentioning
confidence: 99%
“…In chinchillas, the magnitude of the compound action potential decreases the cochlear microphonic amplitude increases during periods of visual attention (Delano et al, 2007). In the IC of awake behaving ferrets, there is task-related modulation of neural ressponses (Slee and David, 2015). Modulation of BOLD responses localized to IC during selective attention has also been reported in human listeners (Rinne et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Cochlear sensitivity, as measured by compound action potentials obtained from a round-window electrode in the chinchilla, was reduced when animals deployed visual attention compared to when animals performed an auditory-only task (Delano et al, 2007). The spectrotemporal tuning of neurons in IC has also been observed to change during detection tasks relative to when animals are passively listening (Slee and David, 2015). Yet despite these results from animal studies, there are not consistent reports of attention-related modulation of subcortical neuroelectrical activity in human listeners.…”
Section: Introductionmentioning
confidence: 99%